Linkage and candidate gene studies of autism spectrum disorders in European populations. - Holt, R; Barnby, G; Maestrini, E; Bacchelli, E; Brocklebank, D; Sousa, I; Mulder, E; Kantojärvi, K; Järvelä, I; Klauck, S; Poustka, F; Bailey, A; et al. (2010)
Over the past decade, research on the genetic variants underlying susceptibility to autism and autism spectrum disorders (ASDs) has focused on linkage and candidate gene studies. This research has implicated various chromosomal loci and genes. Candidate gene studies have proven to be particularly intractable, with many studies failing to replicate previously reported associations. In this paper, we investigate previously implicated genomic regions for a role in ASD susceptibility, using four cohorts of European ancestry. Initially, a 384 SNP Illumina GoldenGate array was used to examine linkage at six previously implicated loci. We identify linkage approaching genome-wide suggestive levels on chromosome 2 (rs2885116, MLOD=1.89). Association analysis showed significant associations in MKL2 with ASD (rs756472, P=4.31 x 10(-5)) and between SND1 and strict autism (rs1881084, P=7.76 x 10(-5)) in the Finnish and Northern Dutch populations, respectively. Subsequently, we used a second 384 SNP Illumina GoldenGate array to examine the association in seven candidate genes, and evidence for association was found in RELN (rs362780, P=0.00165). Further increasing the sample size strengthened the association with RELN (rs362780, P=0.001) and produced a second significant result in GRIK2 (rs2518261, P=0.008). Our results strengthen the case for a more detailed study of the role of RELN and GRIK2 in autism susceptibility, as well as identifying two new potential candidate genes, MKL2 and SND1.